Dominasi Faktor Kepemimpinan dan Sumber Daya Manusia (SDM) dalam Keunggulan Kompetitif Sekolah: Systematic Literature Review - Anindita Nurfitriani; Rahmania Utari (JAMP : Jurnal Administrasi dan Manajemen Pendidikan, 2025)
Abstract: Competition among educational institutions requires schools to excel not only in academic outcomes but also in developing sustainable competitive advantage. This study aims to identify the dominance of leadership and human resource (HR) factors in building schools’ competitive advantage, examine research trends in terms of methods and locus, and synthesize the key factors influencing competitiveness. The study employed a Systematic Literature Review (SLR) by analyzing seven scientific articles published between 2020 and 2025 from Google Scholar and ScienceDirect databases, following predetermined inclusion and exclusion criteria. The synthesis results reveal that schools’ competitive advantage is predominantly determined by the effectiveness of strategic leadership and sustainable HR management. Common strategies include strengthening teacher competencies, fostering adaptive organizational culture, and optimizing intellectual capital components such as human capital, structural capital, and social capital through the Resource-Based View (RBV) framework. Furthermore, research trends on educational competitiveness remain dominated by qualitative and literature-based approaches, with diverse contexts ranging from Islamic schools to higher education institutions. Overall, this study confirms that leadership and human resources are the key determinants of educational institutions’ competitiveness. Future research with empirical approaches is recommended to enhance the validity of findings and deepen understanding of how competitive advantage strategies are implemented across educational levels. Keywords: Competitive advantange; strategic leadership; human resources; Resource-Based View Abstrak: Persaingan antar lembaga pendidikan menuntut sekolah untuk tidak hanya unggul dalam hasil akademik, tetapi juga memiliki keunggulan kompetitif yang berkelanjutan. Penelitian ini bertujuan untuk mengidentifikasi dominasi faktor kepemimpinan dan sumber daya manusia (SDM) dalam membangun keunggulan kompetitif sekolah, meninjau tren penelitian dari aspek metode dan lokus, serta mensintesis faktor-faktor yang memengaruhi keunggulan tersebut. Pendekatan yang digunakan adalah Systematic Literature Review (SLR) dengan menganalisis tujuh artikel ilmiah terbitan 2020–2025 yang diperoleh dari basis data Google Scholar dan ScienceDirect berdasarkan kriteria inklusi dan eksklusi yang telah ditetapkan. Hasil sintesis menunjukkan bahwa keunggulan kompetitif sekolah secara dominan ditentukan oleh efektivitas kepemimpinan strategis dan pengelolaan SDM yang berkelanjutan. Strategi yang banyak ditemukan mencakup penguatan kompetensi guru, pengembangan budaya organisasi adaptif, serta optimalisasi modal intelektual seperti human capital, structural capital, dan social capital berdasarkan perspektif Resource-Based View (RBV). Selain itu, tren penelitian keunggulan kompetitif di bidang pendidikan masih didominasi pendekatan kualitatif dan studi literatur, dengan konteks beragam mulai dari sekolah Islam hingga pendidikan tinggi. Secara keseluruhan, hasil penelitian ini menegaskan bahwa SDM dan kepemimpinan merupakan faktor utama yang menentukan daya saing lembaga pendidikan. Penelitian lanjutan dengan pendekatan empiris disarankan untuk memperkuat validitas temuan dan memperluas pemahaman tentang implementasi strategi keunggulan kompetitif di berbagai jenjang pendidikan. Kata kunci: Keunggulan Kompetitif; kepemimpinan strategis; sumber daya manusia; Resource-Based View